The Relationship Between the Use of Birth Control Implants and Weight Gain in the Bolaang Mongondow Region - Ni Kadek Karmini; Raden Maria Veronika Widiatrilupi; Anik Purwati (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Implant contraception is one of the long-term birth control methods that is effective in preventing pregnancy. However, the use of implant contraception is often associated with side effects, one of which is weight gain. This weight gain can affect compliance and sustainability of the use of implant contraception in the community. Therefore, it is important to understand the relationship between the use of implant contraception and weight gain in the Bolaang Mongondow area. Objective: This study aims to analyze the relationship between the use of implant contraception and weight gain in acceptors in the Bolaang Mongondow area. Method: This study used a quantitative method with a cross-sectional design. The sample in this study were 30 respondents who were acceptors of implant contraception in the Bolaang Mongondow area. Data collection was carried out through interviews and weight measurements before and after using implant contraception. Data analysis was carried out using the chi-square test with a significance level of p <0.05. Results: The results showed that most respondents experienced weight gain after using implant contraception. Statistical analysis with the chi-square test produced a p-value = 0.009, which means that there is a significant relationship between the use of implant contraception and weight gain. Conclusion: There is a significant relationship between the use of contraceptive implants and weight gain in acceptors in the Bolaang Mongondow area. This weight gain is likely caused by hormonal changes that occur due to the use of contraceptive implants. Suggestion: Further education is needed for prospective acceptors of contraceptive implants regarding possible side effects, including weight gain. In addition, health workers need to provide assistance and weight management strategies, such as education on healthy eating patterns and physical activity, to reduce the impact of contraceptive implant use.